Without merit : a novel - Hoover, Colleen (New York, NY : Atria Books, 2017)
"From the #1 New York Times bestselling author of It Ends With Us and November 9 comes a moving and haunting novel of family, love, and the power of the truth. In Colleen Hoover's gripping novel, reminiscent of the bestselling works of Liane Moriarty and Jojo Moyes, a young woman decides to reveal the dark secrets of her seemingly-happy family before she leaves them behind, but when her escape plan fails, she must deal with the staggering consequences of telling the truth"--
The Voss family live in a repurposed church; the once cancer-stricken mother lives in the basement, the father is married to the mother's former nurse, the little half-brother isn't allowed to do or eat anything fun, and the eldest siblings are irritatingly perfect. Merit Voss collects trophies she hasn't earned and secrets her family forces her to keep. She meets Sagan, wit and unapologetic-- and completely unavailable. Merit decides to shatter their happy family illusion, but is forced to deal with the staggering consequences of telling the truth
Includes questions for discussion
Keywords: Family secrets -- Fiction; Dysfunctional families -- Fiction; Family life -- Fiction; Domestic fiction; Psychological fiction; Domestic fiction